Functional classification and performance in wheelchair basketball - Ceruso, Rosario; D'Isanto, Tiziana; Altavilla, Gaetano; Esposito, Giovanni; Di Domenico, Felice; D'Elia, Francesca (Studia Sportiva, 2022)
Wheelchair basketball players are classified into four classes based on the International Wheelchair Basketball Federation competition system. The aim of this study was to investigate whether the IWBF functional classification for wheelchair basketball was related to different performance field-based tests. Forty wheelchair basketball athletes took part in the study. The players carried out five field tests, three of which were quantitative, related to the three conditional skills (strength, endurance and speed test) and two of the qualitative type (accuracy and shooting ability tests). Pearson's correlation was performed to analyse the correlation between the score obtained from functional classification and the results of the wheelchair performance tests. The IWBF class was not correlated (p <0.05) with any of the tests performed. Players with even major injuries, in their best wheelchair set-up, even achieved better times than upper-class players; therefore, the disability factor in these tests is not an index that determines performance disadvantage. The study shows that the functional classification does not affect the qualitative-quantitative performance, so the disabled athlete with a lower score is not disadvantaged in basketball.